امام ابو عبید قاسم بن سلام کی ’’غریب الحدیث‘‘: ایک مطالعہ - Muhammad Atif Aslam Rao; Abrar Ahmad (Pakistan Journal of Islamic Research)
There are many kinds of ‘ulūm al Ḥadīth. Imām Suyūtī mentioned 93 kinds of Ḥadith sciences in his book. One of the unique kind of ‘ulūm ul Ḥadīth is Gharīb al Ḥadīth. This science of Ḥadīth unrevealed various new dimensions, epistemologies, eloquences, explanations and rhetoric for the scholars of hadith and its sciences. The most well-known and admirable book on these sciences in known as: ’کتاب غرائب الحدیث لامام أبي عبید بن قاسم بن سلام‘ This research study, explores the Introduction and methodology of Gharīb al Ḥadīth by Imām Abū Muhammad Qāsim Bin Sallam. Imam spent about forty years of his life in the research of his science of hadith and wrote a comprehensive book. This research paper is an attempt to analyze and introduce a unique contribution of Imām Qasim bin Sallam. The great contribution of the Imam in the field of Ḥadith sciences is widely recognized and acknowledged by Muḥaddithīn, Mufassirīn, scholars, ‘Ulema and students of Ḥadīth sciences.